Potential role of magnolol: A comprehensive review on its efficacy in managing neurological disorders - Nasrin Sultana; Mohammed Abu Sayeed; Marajul Islam; S.M. Asadul Karim Azad; Sumaiya Binte Tareq; Miskhat-Ul- Jannat; Farzana Yeasmin (Brain Disorders)
Magnolol (MG) is a lignan compound isolated from Magnolia officinalis, renowned for its significant neuroprotective properties include the reduction of amyloid-beta toxicity and the inhibition of apoptotic pathways in neuronal cells. MG has demonstrated beneficial effects in models of Alzheimer’s disease and Parkinson’s disease. Approximately 2–10 % MG was found from the bark of Magnolia species. MG has been a cornerstone of traditional Japanese and Chinese medicine, revered for its therapeutic benefits. This bioactive ingredient is a focal point in neuropharmacological research because it promotes neurite outgrowth, enhances neuronal survival, and mitigates neurological impairments. Such properties underscore its potential in addressing a myriad of neurological conditions, including neurodegenerative diseases, stroke, epilepsy, traumatic brain and spinal cord injuries, and neuropathies. MG is not only potent in alleviating neurological impairments but also exhibits robust protective effects against nervous system damage and toxicity. This comprehensive review elucidates the neuropharmacological potential of MG, exploring into its sources, chemical composition, pharmacokinetics, and toxicity, while addressing the challenges and prospects associated with its therapeutic applications. MG's multifaceted benefits underscore its promise as a pivotal agent in neuropharmacology.